Cities, Climate Change and Multilevel Governance - Corfee-Morlot, Jan (OECD Environment Working Papers, 2009)
Cities represent a challenge and an opportunity for climate change policy. As the hubs of economic activity, cities generate the bulk of GHG emissions and are thus important to mitigation strategies. Urban planning will shape future trends and the concentration of population, socio-economic activity, poverty and infrastructure in urban areas translates into particular vulnerability to increased climate hazards. City governments and urban stakeholders will therefore be essential in the design and delivery of cost-effective adaptation policies. Further, by empowering local governments, national policies could leverage existing local experiments, accelerate policy responses, foster resource mobilization and engage local stakeholders. This paper presents a framework for multilevel governance, showing that advancing governance of climate change across all levels of government and relevant stakeholders is crucial to avoid policy gaps between local action plans and national policy frameworks (vertical integration) and to encourage cross-scale learning between relevant departments or institutions in local and regional governments (horizontal dimension). Vertical and horizontal integration allows two-way benefits: locally-led or bottom-up where local initiatives influence national action and nationally-led or top-down where enabling frameworks empower local players. The most promising frameworks combine the two into hybrid models of policy dialogue where the lessons learnt are used to modify and fine-tune enabling frameworks and disseminated horizontally, achieving more efficient local implementation of climate strategies